Distinguishing different animal fat contaminations in sunflower oil by differential scanning calorimetry - Marikkar, Jalaldeen Mohammed Nazrim; Mat Hashim, Dzulkifly; Mohd Zaki, Nor Nadiha; Che Man, Yaakob (Halal Products Research Institute, Universiti Putra Malaysia, 2009)
Mixing of animal fats especially lard and tallow in any form in food products is a cause of concern for certain religions. In this study, the use of differential scanning calorimetric heating thermograms for monitoring the presence of natural lard (LD), beef tallow (BT), and chicken fat(CF) as adulterants in sunflower oil was investigated. Sunflower oil samples spiked separately with LD, BT, and CF in levels ranging from 1 to 20% (w/w) were analyzed using DSC to obtain their heating profiles. The results showed that presence of both LD and BT in sunflower oil tended to cause adulteration peaks in the higher temperature region of heating thermogram while CF adulteration caused changes only in the exiting thermal transitions in the low temperature region. The distinction between LD and BT adulterations could be made easily as there were many characteristic differences between them with respect to their peak size, shape and position.